2021
DOI: 10.1111/jocd.14471
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐injection ultrasound scanning for treating temporal hollowing

Abstract: Background Hyaluronic acid filler injection is commonly administered to correct temple hollowness, typically through deep temporal injection. Since the vascular distribution at the injection site can be diverse, studies on avoiding damage to the corresponding blood vessels are needed. Aims To assess the commonly used hyaluronic acid filler injection site in the temple region, 1cm lateral and 1 cm above from the end of eyebrow, using a Doppler ultrasound to detect any anatomic variations in the blood vessels. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…15 However, our previous study showed that there is a possibility of perforation of the superficial and deep temporal arteries. 16 Our sonographic findings showed that the anterior branch of the deep temporal artery could be interrupted when deeply injected into the temple area (►Fig. 7).…”
Section: Temple Augmentationmentioning
confidence: 77%
“…15 However, our previous study showed that there is a possibility of perforation of the superficial and deep temporal arteries. 16 Our sonographic findings showed that the anterior branch of the deep temporal artery could be interrupted when deeply injected into the temple area (►Fig. 7).…”
Section: Temple Augmentationmentioning
confidence: 77%
“…The temple vessels can be detected using Doppler ultrasonography, and we believe that the safest layers for the temple augmentation are those between the STF and DTF. In our previous study, pre‐injection Doppler ultrasonography allowed immediate pre‐procedural identification of the blood vessels located in a relative, objective, and straightforward manner to avoid complications in the patients receiving the temple injections 16 …”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, pre-injection Doppler ultrasonography allowed immediate pre-procedural identification of the blood vessels located in a relative, objective, and straightforward manner to avoid complications in the patients receiving the temple injections. 16 The first limitation of this study is that the anatomical variability between races was not considered. Second, this study had a small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, treatment in the temporal region is a high-risk task 2 . Understanding the temporal anatomical features can help us to reduce the risks with temporal injection, whereas cadaver anatomy and in vivo ultrasound detections can help us to fully understand the temporal anatomy 3–6 …”
mentioning
confidence: 99%